Autophagy Participates in Lysosomal Vacuolation-Mediated Cell Death in RGNNV-Infected Cells - Huang, Youhua; Zhang, Ya; Liu, Zetian; Liu, Chuanhe; Zheng, Jiaying; Qin, Qiwei; Huang, Xiaohong (Frontiers in Microbiology, 2020)
Nervous necrosis virus (NNV) is the etiological agent of viral nervous necrosis (VNN), also known as viral encephalopathy and retinopathy (VER), which results in heavy economic losses to the aquaculture industry worldwide. Dramatic cytoplasmic vacuoles were observed during NNV infection both in vitro and in vivo; however, the origin and mechanism of cytoplasmic vacuolization remains unknown. In this report, we found that the cytoplasmic vacuole morphology became fused and enlarged during infection with red spotted grouper nervous necrosis virus (RGNNV), which was accompanied by increased cell death. Notably, Lyso-Tracker, but not Mito-Tracker or ER-Tracker, was accumulated in the vacuoles, and abnormal lysosome swelling was observed in RGNNV-infected cells, suggesting that the cytoplasmic vacuoles originated from lysosomal organelles. Cytoplasmic vacuolization and cell death in RGNNV-infected cells was completely blocked by the vacuolar H+-ATPase inhibitor (bafilomycin A1), and was significantly weakened by chloroquine (CQ), a lysosomotropic agent that induces the acidification of the lysosomes. This suggests that lysosome acidification was essential for vacuole formation. Significant inhibitory effects on vacuolization and cell death were also observed in the RGNNV-infected cells following treatment with nigericin and monensin (ionophores that uncouple the proton gradient present in lysosomes). This indicated that lysosome function was tightly associated with RGNNV infection-induced cell death. In addition, vacuoles were found to be partially co-localized with GFP-LC3II punctate dots during RGNNV infection. Moreover, the severity of vacuolization and cell death were both significantly decreased after treatment with the autophagy inhibitor, 3-MA, suggesting that autophagy was involved in lysosomal vacuolization and cell death evoked by RGNNV infection. Thus, our results demonstrate that autophagy participates in lysosomal vacuolation-mediated cell death during RGNNV infection, and provides new insight into our understanding of the potential mechanisms underlying nodavirus pathogenesis in vitro.